School-based promotion of physical literacy: a scoping review - Grauduszus, Martin; Koch, Lennart; Wessely, Stefanie; Joisten, Christine (Frontiers in Public Health, 2024)
Introduction: The role of physical activity in children’s healthy development is undisputed, with school-based interventions being seen as a priority. The promotion of physical literacy (PL) seems to be promising due to its holistic approach, combining physical, cognitive, and affective domains. To develop recommendations for possible measures, we compiled existing literature on existing school-based PL interventions. Methods: Five databases (MEDLINE, Web of Science, SPORTDiscus, ERIC, and PsycInfo) were searched between July 6 and July 10, 2023, by combining the terms “physical literacy,” “school,” “program,” “workshop,” “intervention,” and “curriculum” as well as a manual search. Records were screened in a two-stage process by two independent authors using a priori criteria. Eligible studies concerned PL interventions in the school context. The included records were sorted according to school type/population, structure, content, PL domains addressed, and evaluation. Results: In total, 706 articles were found through the database search and an additional 28 articles through the manual search. After removing duplicates, 502 publications remained, which were screened by title and abstract, leaving 82 full texts. These were cut down to 37 articles describing 31 different programs (19 in primary schools, eight in secondary schools, one in both primary and secondary schools, and three unspecified). Most interventions were conducted during physical education classes (n = 12). All three PL domains were addressed by five interventions, while 11 interventions solely concerned the physical domain. In addition, 21 interventions evaluated their effects on PL. Most evaluations showed small to moderate but inconsistent effects on several PL-related constructs (e.g., self-efficacy, motivation, movement skills). Interventions incorporating all three domains reported positive effects on physical competence and enjoyment. Discussion: Although there is a growing body of data related to school-based PL promotion, their effects and practical application remains relatively underdeveloped: study designs, study quality, PL assessments, and results are heterogeneous. Corresponding research adhering to the holistic approach of PL will be crucial in clarifying the potential lifelong role of PL in promoting physical activity, increasing health and well-being and to actually enable development of recommendations for action.